Academic Self-Efficacy, Social Support, and Professional Identity Among Preservice Special Education Teachers in China - Chen, Xiaomeng; Zhong, Jingxun; Luo, Manli; Lu, Minghui (Frontiers in Psychology, 2020)
The relationship among the social support, professional identity, and academic self-efficacy (ASE) of Chinese preservice special education teachers are explored by measuring the perceived social support, professional identity, and ASE of 302 undergraduate students. Results of the multiple regression are as follows. (1) A significant positive correlation exists among ASE, social support, and professional identity. When preservice special education teachers perceive social support, they have a high sense of professional identity and high ASE. (2) Professional identity exerts a mediating effect on the relationship between social support and ASE. In particular, social support positively influences ASE via professional identity. The results are discussed at the end of this paper and recommendations for improving the ASE of preservice special education teachers are presented.